Analysis and Simulation of Workspace of Humanoid Manipulator based on Matlab - Qingsong Zhang; Shuaichen Duan; Re Xia (Jixie chuandong, 2020)
Taking the humanoid manipulator as the research object and its workspace is analyzed. The screw theory is used to establish the forward kinematics model of the manipulator. At the base of Monte Carlo method，the workspace point-cloud of the manipulator is obtained. The method of combining partitioning by angle method with two-parameter arctangent function is employed to extract the boundary points of the workspace. The least square method is applied to fit the extracted boundary points. The workspace of the manipulator is obtained. The results of the Matlab simulation show that the extraction effect of boundary points is good，and that fitting error of the curve is small，which lays a foundation for the subsequent trajectory planning and motion control of the humanoid manipulator. On the basis，taking the handling of objects as a study case，the collaborative work of the double humanoid manipulator is briefly analyzed.